Industry 4.0 evaluation model for the sugar agroindustry - Jonás Michel- Horta; Loraine Mayrim Giraud- Herrera (Revista UIS Ingenierías)
Industry 4.0 has been gradually implemented across all productive sectors today and the sugar agroindustry is no exception; however, there are still gaps to close. This study presents an Industry 4.0 maturity evaluation model for the sugar cane sector. Although there are several evaluation models of this type, there is no one focused on this type of industry. The methodology consists of 3 stages: the review of existing literature to substantiate the construction of the model, followed by the development and structuring of the industry 4.0 evaluation model for the sugar industry, with specific considerations for application areas, and concluding with the application of the model in a case study. Finally, this work presents an Industry 4.0 evaluation model for the sugar sector, which can be used to evaluate the level of maturity of these organizations concerning Industry 4.0.